2013
DOI: 10.1158/0008-5472.sabcs13-s1-04
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S1-04: A phase II study of adjuvant paclitaxel (T) and trastuzumab (H) (APT trial) for node-negative, HER2-positive breast cancer (BC)

Abstract: Background: Four large randomized phase III trials have reported significant improvements in disease-free (DFS) and overall survival for H administered with adjuvant polychemotherapy for HER2-positive high-risk BC. With the success of HER2-targeting, limiting chemotherapy is both reasonable and feasible, particularly for smaller, node-negative tumors. However data are limited. Methods: APT is a single arm three-stage, multicenter, phase II study of TH. Patients (pts) with HER2-positive BC (IHC 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 0 publications
0
19
0
3
Order By: Relevance
“…In the apt trial, 406 patients with node-negative, her2-positive tumours less than 3 cm in size were treated with weekly paclitaxel plus trastuzumab for 12 weeks, and then with every-3-weeks trastuzumab for 9 months. Recently presented early study results showed 98.7% disease-free survival at 3 years of follow-up 15 . The most common grade 3 or 4 adverse events were neutropenia (5% of patients) and neuropathy (3% of patients).…”
Section: Discussionmentioning
confidence: 98%
“…In the apt trial, 406 patients with node-negative, her2-positive tumours less than 3 cm in size were treated with weekly paclitaxel plus trastuzumab for 12 weeks, and then with every-3-weeks trastuzumab for 9 months. Recently presented early study results showed 98.7% disease-free survival at 3 years of follow-up 15 . The most common grade 3 or 4 adverse events were neutropenia (5% of patients) and neuropathy (3% of patients).…”
Section: Discussionmentioning
confidence: 98%
“…The three-year DFS rate was 98.7% (98% for patients with tumors >1 cm and 99.5% for those with tumors 61 cm), and the three-year RFS was 99.2%. After a median follow-up of 3.6 years, only 10 in a total of 406 patients experienced a recurrence or death, accounting for 2.5% of the population [44]. There are several limitations of this trial, such as the lack of randomization, the inclusion of patients with T1a tumors that are already associated with a very favorable prognosis and the predominance (67%) of HR+ tumors, among which recurrences can be expected beyond the time of follow-up for this study.…”
Section: Her-2-positive ''Small'' Tumorsmentioning
confidence: 99%
“…Mit dem Ziel, eine verträgliche Chemotherapie bei kleinen HER2-positiven Mammakarzinomen (<1 cm), die eine vergleichsweise problematische Prognose haben (bis zu 20% Rückfälle in den ersten 5 Jahren), zu entwickeln, wurde ein alleiniges Paclitaxel-Trastuzumab-Schema vorgestellt (Pac q1w *12 plus Trastuzumab 1 Jahr; [28] …”
Section: Therapie Des Kleinen Her2-positiven Mammakarzinomsunclassified